The Influence Of Technology Orientation On Performance Is Mediated By Innovation In MSMES Results From Melinjo Processing In Menes Banten - M. Fadhli Nursal; Maidani Maidani; Chistophorus Indra Wahyu Putra (UNIVED Press, 2024)
This study analyzes the role of mediation of innovation in the influence of, technological orientation on the performance of MSMEs melinjo in the village of Menes Pandeglang, Banten. This research uses quantitative methods and statistical analysis tools in the form of smartpls 4.0. This study used a sampling technique in the form of accidental sampling as many as 90 entrepreneurs who processed melinjo. The results of this study found that there was an mediating of innovation on influence of technology orientation on performance of MSMEs melinjo in the village of Menes Pandeglang, Banten. Other results explain that the no influence of technology orientation on performance in direct effect. This research focuses on the role of performance of MSMEs processed melinjo. In addition, the focus of this research is on the village of Menes, which is one of the villages in Pandegelang, Banten. The novelty in this study is that apart from the object of research, it is also a research model that has never been studied before.